ON A SPECIFIC FEATURE OF L. TOLSTOY’S POETICS AND ITS SUCCESSORS IN THE LITERATURE OF XX CENTURY. - GONCHAR, NATALYA (Bulletin of Yerevan University H: Russian Philology, 2020)
This article has for an object to show the great importance of autobiographical material, writer’s own life, emotional and spiritual experience in Lev Tolstoy’s creative work, poetics, artistic skill, as well as to illustrate how Tolstoy’s model of employing his own life material was echoed in the 20th-century literature. The proposed theses are underpinned by references to many of Tolstoy’s texts (in particular, by observing the history, composition, details of his novel Anna Karenina), as well as to some of his wordings and sayings. Additionally, the article examines the further development of Tolstoy’s model, presents several examples from Russian, American, and Armenian literature.
Keywords: Tolstoy, creative principles, poetics, autobiographical material, writer’s own experience, Tolstoy’s lessons, successors